Meningkatkan Hasil Belajar Dan Keterampilan Berpikir Kritis Siswa Muatan PKN Menggunakan Model Lebah - Latifah, Nur; Rafianti, Wahdah Refia (CV. ITTC INDONESIA, 2023)
The research problem is low learning outcomes and critical thinking skills. The reason is that students find it difficult to understand concepts, learning is monotonous, less involved, slow to think and teachers have not used varied models. Efforts to overcome this with the